EKSPLORASI PEMAHAMAN MATERI IPAS PADA SISWA KELAS IV MELALUI PENDEKATAN PEMBELAJARAN BERBASIS OBJEK NYATA - Ni Kadek Kayani; Marsono Marsono; I Kadek Widiantana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Science and Social Studies (IPAS) learning in elementary schools still requires strategies that connect concepts with authentic experiences so that students can construct more meaningful understanding. The use of real objects as learning resources is one approach that enables learning activities to be closely related to students’ daily environment. This study aimed to describe the implementation of real object-based IPAS learning and explore the learning experiences of fourth-grade students at SD Negeri 6 Batur in understanding IPAS content. This study employed a qualitative descriptive approach. The participants consisted of the principal, the fourth-grade teacher, and fourth-grade students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and analyzed qualitatively using source and technique triangulation to ensure data trustworthiness. The findings revealed that real object-based IPAS learning was implemented through interconnected stages of planning, implementation, and evaluation. During the learning process, students actively observed, discussed, asked questions, and presented the results of their observations, enabling them to develop concrete learning experiences and construct conceptual understanding based on direct observation. A distinctive finding of this study is that direct interaction with real objects not only increased students’ learning engagement but also encouraged active inquiry, strengthened conceptual understanding, and improved their ability to relate IPAS concepts to real-life situations. These findings indicate that the use of real objects supports contextual learning and provides an effective instructional alternative that aligns with the characteristics and developmental needs of elementary school students. ABSTRAK Pembelajaran IPAS di sekolah dasar masih memerlukan strategi yang mampu menghubungkan konsep dengan pengalaman nyata agar siswa memperoleh pemahaman yang lebih bermakna. Pemanfaatan objek nyata sebagai sumber belajar menjadi salah satu pendekatan yang dapat menghadirkan pembelajaran yang lebih dekat dengan lingkungan siswa. Penelitian ini bertujuan mendeskripsikan pelaksanaan pembelajaran IPAS berbasis objek nyata serta mengeksplorasi pengalaman belajar siswa kelas IV SD Negeri 6 Batur dalam memahami materi IPAS. Penelitian menggunakan pendekatan kualitatif dengan jenis deskriptif. Subjek penelitian meliputi kepala sekolah, guru kelas IV, dan siswa kelas IV yang dipilih secara purposive. Data diperoleh melalui observasi, wawancara semi terstruktur, dan dokumentasi, kemudian dianalisis secara kualitatif dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa pembelajaran IPAS berbasis objek nyata dilaksanakan melalui tahap perencanaan, pelaksanaan, dan evaluasi yang saling berkaitan. Selama pembelajaran, siswa terlibat aktif dalam mengamati, berdiskusi, bertanya, dan mempresentasikan hasil pengamatan sehingga memperoleh pengalaman belajar yang konkret dan membantu membangun pemahaman materi berdasarkan pengamatan langsung. Temuan utama penelitian menunjukkan bahwa pemanfaatan objek nyata tidak hanya meningkatkan partisipasi aktif siswa, tetapi juga memfasilitasi pembelajaran berbasis inkuiri melalui kemampuan siswa mengidentifikasi konsep secara mandiri, mengaitkan materi dengan situasi kehidupan sehari-hari, serta mempertahankan pemahaman konsep secara lebih bermakna berdasarkan pengalaman autentik.